Characterizing the Journey of Early Alzheimer’s Disease in Patients Initiating Lecanemab Treatment in the United States: A Real-World Evidence Study - Marwan N. Sabbagh; Chenyue Zhao; Malena Mahendran; Se Ryeong Jang; François Laliberté; Hideki Toyosaki; Kaixin Zhang; Feride Frech; Kavita V. Nair (Neurology and Therapy)
Abstract Introduction With the advent of disease-modifying therapies for early Alzheimer’s disease (AD), a comprehensive characterization of patients initiating lecanemab in the USA is needed to understand its use in real-world settings. Methods This retrospective observational study used administrative claims from the Komodo Research Database (1/1/2023–6/30/2024). Eligible patients had ≥ 1 lecanemab administration (first claim defined the index date) and ≥ 12 months of clinical activity/insurance eligibility before the index date. Patient characteristics, diagnostic process, and AD-related medications were evaluated within 12 months before the index date (baseline), whereas lecanemab treatment patterns and concomitant medications were evaluated on or after the index date (follow-up). Outcomes were reported using descriptive statistics and persistence to lecanemab was evaluated using Kaplan–Meier analysis. Results Of 3155 patients included in the study, mean age was 75.0 years, 55.8% were female, 44.2% were male, and most (93.3%) received their index lecanemab administration in an urban setting. Diagnoses of AD (83.8%) and mild cognitive impairment (60.8%) were common at baseline, and 67.6% of patients used AD symptomatic medications. Average time from earliest diagnosis to first lecanemab administration was 4.9 months among patients with a diagnosis in January 2023 (accelerated approval date) or onwards. Over a mean follow-up of 138.8 days, the monthly mean number of administrations of lecanemab was 1.9, with an average of 16.5 days between consecutive administrations and 47.4 days to the first follow-up head magnetic resonance imaging. Persistence to lecanemab was 87.6% at 4 months after treatment initiation. Conclusion Lecanemab was utilized in appropriate patient populations according to the prescribing information approved by the US Food and Drug Administration. Findings from our study provide first insights into the real-world use of lecanemab in the USA and shed light on the need for increased and timely lecanemab initiation for the long-term management of early AD.